Through, lapped or blind: the dovetail joint in furniture history - Clive Edwards (2012)
Furniture joints can tell historians, conservators and curators much about the history of a piece. Although there are many varieties of wood working joints, it is often the dovetail that is seen as the quintessential cabinet-makers’ joint. Indeed, even to the nonprofessional, the dovetail is one of the most recognisable joints in furniture. Considered one of the strongest of cabinet joints, whether hidden or exposed, it so often reflects quality and artisanship. Ranging from the elementary to the complex, the dovetail joint has a number of variations from the simply functional to the clearly decorative. This paper considers the origins of the dovetail from ancient Egyptian cabinetwork, through its development as a builders’ and joiners’ joint, to becoming the symbol of refined cabinet making. It will consider the applications of the joint in both hand and machine-cut versions. Of particular interest are the attempts to mechanise the method of dovetail joint cutting. The nineteenth century in particular has left a legacy of patented processes and developments that show us how creating dovetails changed from a skilfully crafted hand operation to a simple and speedy machine process using the modern-day router and jig combinations. The development of this simple, though sophisticated joint and its many variations, is a fascinating story.